1997
DOI: 10.1159/000196721
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial Asthma and Airway Hyperresponsiveness at High Altitude

Abstract: The mountain climate can modify respiratory function and bronchial responsiveness of asthmatic subjects. Hypoxia, hyperventilation of cold and dry air and physical exertion may worsen asthma or enhance bronchial hyperresponsiveness while a reduction in pollen and pollution may play an important role in reducing bronchial inflammation. At moderate altitude (1,500-2,500 m), the main effect is the absence of allergen and pollutants. We studied bronchial hyperresponsiveness to both hyposmolar aerosol and methachol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 19 publications
2
31
1
1
Order By: Relevance
“…One problem with this study, however, was the fact that all subjects received either dexamethasone or acetazolamide at the highest elevation, which might have affected bronchial hyperreactivity. COGO et al [147] reached a different conclusion than LOUIE and PARE [146]. They studied 11 mild asthmatic patients at sea level and 5,050 m and demonstrated decreased bronchial reactivity to both hypoosmolar aerosol and methacholine at high altitude.…”
Section: Air Densitymentioning
confidence: 95%
“…One problem with this study, however, was the fact that all subjects received either dexamethasone or acetazolamide at the highest elevation, which might have affected bronchial hyperreactivity. COGO et al [147] reached a different conclusion than LOUIE and PARE [146]. They studied 11 mild asthmatic patients at sea level and 5,050 m and demonstrated decreased bronchial reactivity to both hypoosmolar aerosol and methacholine at high altitude.…”
Section: Air Densitymentioning
confidence: 95%
“…The remaining 35 studies underwent further review. Critical review of complete texts of the 35 eligible studies identified two publications [9,10] that were excluded because they were based on data ultimately subsumed in two other publications [11,12]. We also found that a study set of one publication [13] was included within a larger cohort [14], so only the latter was included.…”
Section: Data Sources and Searchesmentioning
confidence: 99%
“…Main factors that are suggested to influence asthma in high-altitude climate therapy are allergen avoidance, increased cortisol and catecholamine level, the dry air and high UV light exposure [15][16][17][18]. However, only little is known about the underlying immunological mechanisms [19,20].…”
Section: Introductionmentioning
confidence: 99%